THU0301 Safety following initiation of rituximab in granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA): interim analysis of the rituximab in anca-associated vasculitis registry (RAVER). (15th June 2017) - Niles, J; Allen, N; Block, JA; Koening, CL; Langford, CA; Abril, A; Lee, AS; Merkel, PA; Mertz, LE; Monach, PA; Moreland, LW; Nachman, PH; et al.
Abstract : Background: Therapy-related serious adverse events (SAEs) are important causes of morbidity in patients with GPA or MPA. Long-term safety data of rituximab in GPA/MPA are limited. Objectives: To characterize safety events in an observational registry of patients with GPA/MPA initiating rituximab. Methods: This interim analysis of RaVeR, an ongoing open-label real-world study of adult patients with GPA or MPA initiating rituximab (dose/frequency determined by investigator), was conducted when 50% of patient-years (PY) were collected (July 2015). Safety events included serious infections (SI), infusion-related reactions (IRR), serious cardiac events, malignancies, and other serious events. Crude incidence rates (IR) and 95% CI were calculated. Trial registration number: NCT01613599 Results: 97 patients (291 PY) received rituximab, of whom 70% received rituximab retreatment. Median follow-up was 2.4 years. Overall, 91% of patients were ANCA-positive and 78% had GPA. 17 patients (17.5%) had a history of plasmapheresis or dialysis; 20 (20.6%) were receiving rituximab plus cyclophosphamide at baseline. 33 patients had 71 SAEs (32.4/100 PYs [95% CI: 25.32–40.89]). 11 patients had 20 SIs (9.13/100 PYs [95% CI: 5.58–14.10]). 9 patients (9.3%) experienced 13 serious cardiovascular (CV) events (5.93/100 PYs [95% CI: 3.16–10.15]), 12 of which were reported as unrelated to rituximab. Of the 13 CV events, 9 were atrial arrhythmias and most patients had associated renal or CV disease history. There were no serious IRRs or SAEs within 24 hours of rituximab infusion. There were 6 deaths (2.74/100 PYs [95% CI: 1.01–5.96]); causes of death included septic shock, interstitial lung disease, congestive heart failure, cardio-respiratory arrest and 2 deaths of unknown etiology. The severe disease flare rate was 5.94/100 PYs (95% CI: 3.16–10.15). Among patients who received rituximab retreatment, the IRs of SAEs (26.1/100 PYs) and SIs (7.29/100 PYs) were not increased compared with the overall cohort. Conclusions: In this interim analysis of patients with GPA/MPA treated with rituximab, SAEs were not increased compared with comparable cohorts of patients with renal involvement. Safety events did not increase with rituximab retreatment. These results are consistent with the known safety profile of rituximab and provide preliminary long-term, practice-level safety data for rituximab in GPA/MPA. Acknowledgements: This study was funded by F. Hoffmann-La Roche, Ltd. Disclosure of Interest: J. Niles: None declared, N. Allen Grant/research support from: Genentech, Inc., J. Block: None declared, C. Koening Grant/research support from: VA Merit, C. Langford: None declared, A. Abril: None declared, A. Lee: None declared, P. Merkel: None declared, L. Mertz: None declared, P. Monach Grant/research support from: Genentech, Inc.; Bristol-Meyers Squibb; GlaxoSmithCline, Speakers bureau: Medscape, L. Moreland Grant/research support from: Genentech, Inc.; Pfizer; Bristol-Meyers Squibb, Consultant for: Pfizer; Boehringer Ingeheim, P. Nachman: None declared, T. Peikert: None declared, R. Spiera: None declared, D. Wallace: None declared, F. Erblang Employee of: F. Hoffmann-La Roche, Ltd., M. Cascino Employee of: Genentech, Inc., P. Duncombe Shareholder of: prn Statistical Consulting Services, Ltd., V. Malik Employee of: F. Hoffmann-La Roche, Ltd., P. Brunetta Employee of: Genentech, Inc.